2017
DOI: 10.3414/me16-01-0135
|View full text |Cite
|
Sign up to set email alerts
|

Mining Major Transitions of Chronic Conditions in Patients with Multiple Chronic Conditions

Abstract: These findings suggest that our proposed LRMCL algorithm can be used to describe and understand MCC transitions, which may ultimately allow healthcare systems to support optimal clinical decision- making. This method will be used to describe a broader range of MCC transitions in this and non-VA populations, and will add treatment information to see if models including treatments and MCC emergence can be used to support clinical decision-making in patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…There is significant diversity in the definition of “patterns” in multimorbidity research, with some studies employing a temporal component 25 , 107 , 111 , 117 , 118 and others using the term almost synonymously with patient clusters. 63 Methods used to discern accumulation were highly heterogeneous and showed novel applications of advanced statistical techniques. A common feature of the five articles was the use of diagrams to demonstrate temporal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the second block of rows in Table 4 illustrates the prediction accuracy of year-3 to year 5 comorbidities, given year-1 and year-2 comorbidities. Except for the LRMCL method, which can only incorporate the comorbidity information of the immediate preceding year [ 12 ] (See first block of rows in Table 4 ), for all other competing methods, we collect the information of AUC performance for various years of given comorbidities, namely year 1 to year 4. As shown in Table 4 , the MTBNs provides the best performance across all competing methods, followed by the probit and logistic regression and finally LRMCL.…”
Section: Resultsmentioning
confidence: 99%
“…Pugh et al [ 11 ] showed that these comorbidity phenotypes are associated with measures of community reintegration, with individuals in the PCT and Mental Health groups being significantly more likely to report difficulty in the transition from military to civilian life, lower levels of social support, and higher rates of unemployment. Alaeddini, et al [ 12 ] developed a Latent Regression Markov Mixture Clustering (LRMCL) algorithm to identify major transitions of four MCC that include hypertension (HTN), depression, PTSD, and back pain in a cohort of 601,805 Iraq and Afghanistan war Veterans (IAVs). The LRMCL algorithm was also able to predict the exact status of comorbidities about 48% of the time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation